Multivariate Analysis of Factors Influencing Students’ Performance and Self-Efficacy in Mathematics - Olagoke, Michael (Desimal: Jurnal Matematika, 2026)
Mathematics performance and self-efficacy are critical indicators of students’ academic readiness, particularly in secondary education where Mathematics functions as a gateway to science, technology, vocational, and higher education pathways. This study examined teacher-related factors influencing secondary school students’ Mathematics performance and self-efficacy in Ekiti State, Nigeria, using a multivariate analytical framework. A quantitative descriptive correlational survey design was employed, supported by multiple regression and path analysis. The population comprised 13,231 Senior Secondary School II and III students and 1,320 Mathematics teachers in public secondary schools. Through a multistage sampling procedure, 388 students and 132 Mathematics teachers were selected. Data were collected using the Teacher Variables, Students’ Performance and Self-Efficacy in Mathematics Questionnaire, which produced a reliability coefficient of 0.87. Descriptive findings showed that students’ Mathematics performance was generally moderate, with a mean score of 56.4, while Mathematics self-efficacy was also moderate, with an overall mean of 2.64. Inferential results revealed that teacher-related variables significantly predicted students’ self-efficacy, explaining 41.2% of the variance, and significantly predicted Mathematics performance, explaining 38.2% of the variance. Teacher attitude, content knowledge, classroom management, and performance feedback consistently emerged as the strongest predictors. The integrated path model further indicated a positive relationship between Mathematics performance and self-efficacy, suggesting that achievement and confidence reinforce each other in Mathematics learning. The study contributes by extending social cognitive perspectives into an integrated teacher-variable framework and concludes that sustainable improvement requires teacher development focused on content mastery, supportive pedagogy, classroom organization, constructive feedback, and learner confidence.